ANALISIS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR PAK SISWA KELAS VIII SMP NEGERI 3 MUARA SIATAS BARITA TAHUN PEMBELAJARAN 2019/2020. - masni padang (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
The purpose of this study was to determine the magnitude of the percentage of the application of the jigsaw cooperative learning model in improving PAK learning outcomes of Grade VIII students of SMP Negeri 3 Muara Siatas Barita 2019/2020 Learning Year. The research hypothesis is the analysis of the application of a jigsaw cooperative learning model in improving the learning outcomes of students of class VIII of SMP Negeri 3 Muara Siatas Barita 2019/2020 Learning Year 75% of the expected 100%.               The population in this study were all eighth grade students of SMP Negeri 3 Muara Siatas Barita 2019/2020 Learning Year, totaling 52 people. This research method is quantitative inferential method. The research instrument was a closed questionnaire. Hypothesis testing using the t test formula is obtained value (count) = 10.83 t table = 1.711. The value of t_ count is in the area of the curve of rejection H0 and acceptance of Ha.            Thus it can be concluded that the research hypothesis is accepted, namely the analysis of the application of the jigsaw cooperative learning model in improving the learning outcomes of grade VIII PAK students of SMP Negeri 3 Muara Siatas Barita 2019/2020 Learning Year 75% of the expected 100%. Achievement of the application of the jigsaw cooperative learning model in improving PAK learning outcomes of VIII grade students of SMP Negeri 3 Muara Siatas Barita in the 2019/2020 Academic Year is 3,423 in the good category with a percentage of 85.57% in the very strong category.Keywords: Jigsaw Cooperative Learning Model, PAK Learning Outcomes